(untitled) (Journal of the College of Basic Education, 2025)
This research aims to highlight the importance of sustainable urban planning in Iraq as an urgent necessity to redesign cities and develop infrastructure to address the environmental and social challenges faced by Iraqi cities. The study discusses issues resulting from unplanned growth, infrastructure deterioration, and climate change, emphasizing the need to adopt urban planning strategies focused on sustainability, efficiency, and resilience. The research relies on field studies, scientific analysis, and comparative studies to provide insights and practical recommendations for sustainably re-planning cities, ensuring better quality of life, a healthy environment, and balanced, sustainable urban development in Iraq.